Analisis Peningkatan Produktivitas Kerja Pegawai Melalui Faktor Pelatihan - Zuki Kurniawan; Adie Irwan Kusumah; Neuneung Sadiyah (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2019)
This research is a descriptive verification study using a quantitative approach. The population in this study were all employees of PT. Prunabon Global Supplies Indonesia. The research sample was selected using random sampling techniques to obtain the experimental and control groups. Based on the results of data processing, that PT. Prunabon Global Supplies Indonesia in the training method using the hall method. The results showed that in the experimental group some employees responded positively to training with an average value of 81.26, while the average in the control group was 75.51. The percentage increase from before and after treatment in the experimental group was 10% while the control group was 5.29%. And the statistical hypothesis test shows a significant value (t) 0,000 is smaller than α determined (0.05) or seen from the hypothesis testing criteria obtained t count greater than t table (3.849 ≥ 1.669) thus H0 is rejected and Ha is accepted. This shows that training is very influential in increasing employee work productivity.